Tinjauan Interdisipliner dalam Mengkaji Aspek Kosmologi dalam Arsitektur - Titisari, Ema Yunita; Antariksa, Antariksa; Wulandari, Lisa Dwi; Surjono, Surjono (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
This paper is a review of the importance of interdisciplinary reviews in assessing the cosmological aspects of architecture. Architecture is a discipline that focuses on the study of the human environment. Environment and humans are very complex objects. Studies of people and architecture need to involve other disciplines. Involving other disciplines will help the understanding of people and architecture as a cultural product. Cosmology is the key to understanding architecture, especially the architecture of pre-modern society. By analysing the substance of some theories and architectural research on cosmology obtained the conclusion that in reviewing cosmological aspects in architecture is required interdisciplinary studies because architecture is an object that needs to be viewed from many perspectives. This is due to the complexity of human beings who create and create architecture as a place of residence.Keywords: interdisciplinary, architecture, cosmology